Some Basic Aspects of HLA-G Biology - Estibaliz Alegre; Roberta Rizzo; Daria Bortolotti; Sara Fernandez-Landázuri; Enrico Fainardi; Alvaro González (Journal of Immunology Research)
Human leukocyte antigen-G (HLA-G) is a low polymorphic nonclassical HLA-I molecule restrictively expressed and with suppressive functions. HLA-G gene products are quite complex, with seven HLA-G isoforms, four membrane bound, and other three soluble isoforms that can suffer different posttranslational modifications or even complex formations. In addition, HLA-G has been described included in exosomes. In this review we will focus on HLA-G biochemistry with special emphasis to the mechanisms that regulate its expression and how the protein modifications affect the quantification in biological fluids.